Protective Effect of Isoorientin on Oleic Acid-Induced Oxidative Damage and Steatosis in Rat Liver Cells - Luo, Tongwang; Jiang, Sheng; Zhou, Bin; Song, Quanjiang; Du, Jing; Liu, Ping; Wang, Xiaodu; Song, Houhui; Shao, Chunyan (Frontiers in Pharmacology, 2022)
The harm of nonalcoholic fatty liver disease to human health is increasing, which calls for urgent prevention and treatment of the disease. Isoorientin is an effective ingredient of Chinese herbal medicine with anti-inflammatory and antioxidant effects. However, the effect of isoorientin in nonalcoholic fatty liver disease is still unclear. In this study, combined in vivo and in vitro experiments, through pathological observation, flow cytometry, immunofluorescence and western blot analysis to explore the role of isoorientin in steatosis and reveal its molecular mechanism. The results demonstrated that oleic acid treatment significantly increased the content of ROS and lipid droplets in rat hepatocytes, and promoted the expression of γH2AX, HO-1, PPARγ, SREBP-1c, FAS. The ROS content in the cells of co-treated with isoorientin and oleic acid was significantly reduced compared to the oleic acid group, and the expression of γH2AX, HO-1, PPARγ, SREBP-1c, FAS, and the nuclear translocation of NF-κB p65 were also significantly inhibited. Our data showed that oleic acid induce oxidative damage and steatosis in hepatocytes both in vitro and in vivo, and activate the PPARγ/NF-κB p65 signal pathway. Moreover, isoorientin can significantly reduce oleic acid -induced oxidative damage and steatosis by regulating the PPARγ/NF-kB p65 signal pathway.